QRIS: Factors Influencing Interest in Adoption by MSMEs in Semarang Regency - Jihan Rahmawati; Sri Murtini; Rani Raharjanti; Prima Ayundyayasti (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Abstract The motivation of this research is related to the use of QRIS in micro, small, and medium-sized enterprises (UMKM) in Semarang District. QRIS is a digital payment tool introduced by Bank Indonesia in 2019. The Government's initiative in launching QRIS is to make it easier for people who prefer digital payments, especially young people in Indonesia. The use of QRIS itself is increasing every year. The Governor of Bank Indonesia stated that more than 90% of UMKMs in Indonesia have used QRIS. The benefits of using QRIS for UMKM are faster payment processes, no need to prepare for money returns, increased sales turnover, easier settlement process, and financial discipline. The model used in this study is the Technology Accepted Model (TAM). TAM is a method to measure individual reception to the use of information technology systems. This research uses a quantitative descriptive approach. Micro, small, and medium-sized enterprises (UMKM) are used as populations in this study. In the sample selection, the researchers conducted the dissemination of the questionnaire with two events, namely online and offline. The samples obtained after the implementation of disseminated questionnaires and according to the conditions of the research sample are as many as 210 UMKM. Further, SmartPLS version 4 software is used for data processing. The findings from this study are that product knowledge variables significantly affect the use of QRIS. Perceived usefulness variables have also been found to influence the use. The same thing was also found in the perceived ease of use variable. Other findings that are backward related to the perception of risk variables. On this variable, it has been found that there is a negative influence against the use, so, it can be concluded that UMKM in Semarang district is still afraid related to financial risk as a result of the QRIS use.